2014
DOI: 10.1002/ange.201402661
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Indolen durch ein modifiziertes Koser‐Reagens

Abstract: Eine neue Methode unter metallfreien Bedingungen zur schnellen und produktiven Synthese von Indolen wurde entwickelt. Dieser Prozess beruht auf einer voluminçsen Iodverbindung der Familie der Koser-Reagentien, wobei die Kombination aus Iodosobenzol und 2,4,5-Tris(isopropyl)benzolsulfonsäure die hçchsten Ausbeuten und kürzesten Reaktionszeiten gewährleistet. Dieses Reagens vermittelt die chemoselektive oxidative Cyclisierung von 2-Vinylanilinen zu Indolen in hohen Ausbeuten und unter milden Reaktionsbedingungen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 91 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…As expected from ar elated diamination with hypervalent iodine reagents, [23] the reactionw ith 3e led to the formation of as ingler egioisomeric product 12 a,w hich is the thermodynamically preferred product due to maintenance of the styrene conjugation.2 -Aminostyrene also constitutes an interesting substrate. While its Cbzprotectedd erivative 4t behaves as the styrene derivatives from Scheme 5a nd thus undergoes clean iodooxygenation to 6r,t he corresponding tosylamide 4s promotes an aminooxygenationt ot he 3-oxygenated indoline 12 b.I nterestingly, this product proofed to be stable against indole formation [24] through elimination. Ar elated cyclization was attempted with 11 b as precursor to iodolactonization.…”
Section: Resultsmentioning
confidence: 99%
“…As expected from ar elated diamination with hypervalent iodine reagents, [23] the reactionw ith 3e led to the formation of as ingler egioisomeric product 12 a,w hich is the thermodynamically preferred product due to maintenance of the styrene conjugation.2 -Aminostyrene also constitutes an interesting substrate. While its Cbzprotectedd erivative 4t behaves as the styrene derivatives from Scheme 5a nd thus undergoes clean iodooxygenation to 6r,t he corresponding tosylamide 4s promotes an aminooxygenationt ot he 3-oxygenated indoline 12 b.I nterestingly, this product proofed to be stable against indole formation [24] through elimination. Ar elated cyclization was attempted with 11 b as precursor to iodolactonization.…”
Section: Resultsmentioning
confidence: 99%
“…[11,34] In conclusion, we have demonstrated that the coordination of an ortho-methoxymethyl group effectively stabilizes N-acyliminoiodinanes,e nabling the first synthesis and characterization of their structure.T he X-ray structure revealed that the carbonyl oxygen atom coordinates to the iodine atom of the iminoiodinane.A dditionally,t he N-acyliminoiodinane could be activated to react with silyl enol ethers under photoirradiation conditions.T his method was successfully expanded to various N-sulfonyliminoiodinanes.W eb elieve that the present activation method of iodinanes will encourage greener approaches for the introduction of amino groups, and further develop the understanding of hypervalent iodine chemistry. [35] Further investigation of the detailed reaction mechanism and more diverse applications are now underway in our laboratory.…”
Section: Angewandte Chemiementioning
confidence: 99%